Cross-cultural behaviour in tourism : concepts and analysis - Reisinger, Yvette (Butterworth-Heinemann, 2003)
Cross-Cultural Behaviour in Tourism: Concepts and Analysis is important reading for those in the following areas of industry: * Tourism: illustrates the importance of cultural background in the tourist experience and how it is a major determinant in repeat visitation * Marketing: provides an understanding of the cultural background of a destination that is vital when formulating successful marketing strategies * Management: provides valuable examples on how cultures influence tourist behaviour and decision-making, helping managers to develop cross-cultural skills and deal with tourists from di.